Notes on Some Stone and Flint Implements found near Dryburgh, in the Parish of Mertoun, Berwickshire - Corrie, John (Proceedings of the Society of Antiquaries of Scotland, 1916)
Flakes and spalls are, as might perhaps have been expected, the most numerous relics. They exhibit considerable variation as regards size, material, and flaking, and a good many of them, as indicated by their blunted edges, appear to have been used as knives or scrapers without further chipping. The material is mostly flint, chert, or quartz, but it includes also one or two interesting examples of pitchstone. The main focus of the article is on those artefacts described as pigmy flints which are are remarkable and delicately manufactured implements of crescent, triangular, pointed, and rhomboidal form.